In-situ monitoring of interface proximity effects in ultrathin ferroelectrics - Nives Strkalj (Nature Portfolio, 2020)
How to maintain a robust polarization in ferroelectrics despite its inherent suppression when going to the thin-film limit is a long-standing issue. Here, the authors propose the concept of competitive and cooperative interfaces and establish robust polarization states in the ultrathin regime.